Difficulties of everyday life faced by low-income elders - Narcélia Souza Barbosa; Maria Josefina da Silva; Maira Di Ciero Miranda (Rev Rene)
This study the social and economic standard of elders, identifies their problems or events occurred during their lives and brings up ways of how they deal with each matter. The data was collected through semi-structured interviews, in which 60 elders of a support group took part. As result, we conclude that the stress factor depends on the living experience, the phase of their cycle of life, the existing beliefs, the kind of support they have and their personal resources. Those factors evolve as they get older. The feeling of lost causes an unbalance in the lives of those who experienced it. The strategies of standing up for each situation come from their capacity of problem solving and the social support they receive.